Bibliometric - thematic analysis and a technology-enabler-barrier-based framework for digital supply chain. (22nd February 2023) - Sharma, Vikrant; Anand, Satyajit; Kumar, Mukesh; Pattnaik, Manjula
Digital supply chain is a proactive, value-driven, and efficient process that helps businesses generate new sources of revenue and business value. From 2000 to 2021, this article covers the evolution of digital supply chain research, outlining critical concerns and trends for the future. This analysis aims to undertake a bibliometric analysis of the literature on digital supply chains to identify emerging trends in this subject through a review of the most influential articles, keywords, authors, institutions and countries. Three software tools were used to accomplish this goal: the R package (Bibliometrix R Package), VOSviewer and SciMAT. According to the research, Germany, Turkey, and the USA have the most publications and total citations. Additionally, a framework based on technology, enablers, and barriers is proposed, and a discussion of the future path of the digital supply chain. This study is the first to analyse digital supply chains' evaluation and give a decision-making framework.